2008
DOI: 10.1037/0735-7036.122.3.305
|View full text |Cite
|
Sign up to set email alerts
|

Whistle rates of wild bottlenose dolphins (Tursiops truncatus): Influences of group size and behavior.

Abstract: In large social groups acoustic communication signals are prone to signal masking by conspecific sounds. Bottlenose dolphins (Tursiops truncatus) use highly distinctive signature whistles that counter masking effects. However, they can be found in very large groups where masking by conspecific sounds may become unavoidable. In this study we used passive acoustic localization to investigate how whistle rates of wild bottlenose dolphins change in relation to group size and behavioral context. We found that indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 32 publications
4
91
0
Order By: Relevance
“…LFN sounds were produced during 7 encounters or 12% of encounters with bottlenose dolphins, compared with the 48 (81%) encounters in which whistles were found and 45 (76%) encounters in which BP sounds were identified. Similar proportions have been reported from other sites, for example in the Gulf of Mexico (GOM), LFN sounds were produced during 12% of encounters with dolphins (Simard et al 2011) and in Scotland whistles were identified from 84% of encounters (Quick and Janik 2008).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…LFN sounds were produced during 7 encounters or 12% of encounters with bottlenose dolphins, compared with the 48 (81%) encounters in which whistles were found and 45 (76%) encounters in which BP sounds were identified. Similar proportions have been reported from other sites, for example in the Gulf of Mexico (GOM), LFN sounds were produced during 12% of encounters with dolphins (Simard et al 2011) and in Scotland whistles were identified from 84% of encounters (Quick and Janik 2008).…”
Section: Discussionsupporting
confidence: 81%
“…However, the majority of research has focused on echolocation clicks and whistles (e.g. Au et al 1982;Jones and Sayigh 2002;Quick and Janik 2008;Díaz López 2011) without looking at the whole repertoire of vocal production. Bottlenose dolphin echolocation clicks are high intensity, short duration, broadband sounds with ultrasonic peak frequencies, usually produced in rapid succession (click trains) for the detection and discrimination of targets (Au 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whistles paired with a point sample in which information was missing from the field observations were excluded from any further analysis. To account for the secondary behavioural states involving milling, which may indicate a transition between states (Quick & Janik, 2008), a mixed behavioural state (MIX) was introduced at the analysis stage. It was assigned to point samples where milling behaviour was documented as the primary behaviour with either socializing or surface feeding as the secondary behaviour, or in cases where socializing or surface feeding was the primary behaviour with milling as the secondary behaviour.…”
Section: Acoustic and Behavioural Analysismentioning
confidence: 99%
“…In favourable conditions, these signals can propagate over tens of kilometres (Janik, 2000). Whistle production is usually higher during socializing contexts (Jones & Sayigh, 2002;Quick & Janik, 2008) and when animals experience stress (Esch, Sayigh, Blum, & Wells, 2009). Each bottlenose dolphin uses an individually distinctive signature whistle which is acquired through vocal production learning in the first year of life (Caldwell & Caldwell, 1979;Janik & Slater, 1997).…”
mentioning
confidence: 99%